2011
DOI: 10.1111/j.1600-0668.2011.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of gas-phase trichloramine (NCl3) in chlorinated, indoor swimming pool facilities

Abstract: The activities of swimmers promote transfer of volatile compounds from water to the surrounding air. For chlorinated, indoor pool facilities, this can lead to exposure to gas-phase chemicals that can cause irritation of the respiratory system and other tissues. The focus of this study was on NCl(3), a common disinfection by-product (DBP) in chlorinated pools. However, the conditions that promote NCl(3) transfer are likely to promote transfer of other volatile chemicals from water to air. As such, it is possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 19 publications
5
46
0
Order By: Relevance
“…8,[14][15][16][17] Hypersensitivities to fungus and mites are aggravated by the time spent within the pool area, which leads to cytological changes. The concentrations of chlorine by-products in indoor air, such as trihalomethanes and trichloramine, have been found to be correlated with the concentrations found in the pool water.…”
Section: Discussionmentioning
confidence: 99%
“…8,[14][15][16][17] Hypersensitivities to fungus and mites are aggravated by the time spent within the pool area, which leads to cytological changes. The concentrations of chlorine by-products in indoor air, such as trihalomethanes and trichloramine, have been found to be correlated with the concentrations found in the pool water.…”
Section: Discussionmentioning
confidence: 99%
“…Trichloramine, a common DBP, is a volatile irritant gas. Transfer of this gas from water to the surrounding air is promoted by the dynamic activities of swimmers (Weng et al 2011) and is influenced by factors such as ventilation, air recirculation, and water temperature (Uyan et al 2009). Levels may fluctuate from 0.2 to 0.9 mg/m 3 in indoor pools, depending on occupancy and ventilation, an exposure that is substantially greater when compared to typical air pollutant levels of 0.3 mg/m 3 in non-pool environments (Bernard et al 2006).…”
Section: Effects Of Swimming Pool Exposure On Allergy and Asthmamentioning
confidence: 99%
“…Their results showed that under the influence of volatilization, daytime concentration of THMs in the air of the indoor swimming pool was much higher than at night. In addition, Weng et al (2011a) conducted a study on trichloramine (NCl 3 ), another type of volatile DBP, in indoor swimming pools. Their sampling results showed that every day from 16:00 to 22:00, coinciding with the highest number of swimmers, the concentration of NCl 3 in the air was higher; that is, the number of swimmers and the concentration of volatile DBPs in the air were highly correlated.…”
Section: Association Of Occupant Activities With Variations Of Chloromentioning
confidence: 99%